Predicting Psychological Wellbeing of Iranian Students Based on Attachment Styles and Internet Addiction in the Post-Corona Era - Qanadan, Farzane; Jafarzadeh, Mohammad Rahim (FKIP - Universitas Tanjungpura, 2025)
The purpose of this research was to predict Iranian students' psychological well-being based on attachment styles and Internet addiction. The research design was descriptive and correlational. The current research population included 22131 fourth and fifth-grade students of Dezful City in the academic year